A study of benefit and cost analyis of the composting andthermalde composition for organic waste management - Raden Arief Firmansyah; Khoirul Hidayat (Universitas Darussalam Gontor, 2023)
Awareness of Indonesian people about waste management is low, specifically in organic waste management. Organic waste management is relatively easy. On the other hand, open dumping and open burningare always choices by the community or person. These techniques are not sustainable actions, for the environment, even for living things. Waste could be managed sustainably, i.e., composting and thermal decomposition (pyrolisis). Composting produces organic fertilizer that is saleable and profitable. Thermal decomposition (pyrolysis) potentially have three product, bio-oil, bio-char, and syngas. These products are marketable and promising too. This research aims to study the potential application of composting and thermal decomposition technology on a small-neighborhood scale based on cost-benefit analysis.The study used benefit-cost analyis. Data is collected by literature study, from national and internasional journal, law product and govermnet policies.This study was occupied to one of the urban village in Pamekasan Sub-district, Pamekasan Regency. The study resulted that composting required more areathan pyrolisis. It is a constraint criteria to consider applying composting method in Tempat PengolahanSampah Reduce, Reuse, Recycle (TPS 3R).Sosial cost green house gas (GHG) was the biggest component that contributed to total costabout 95.56%. Meanwhile, in total benefit, benefit sale of product solid waste treatment was the biggestat 80.80%. Pyrolisis was more feasible than composting based on Benefit Cost Ratio (BCR)value. The composting duration was the limitation factor that affect BCR value negative (less than 1). It indicated to sustainabilty running, TPS 3R should be subsidize on investment andoperational cost.To achieve maximal benefit, composting should applied in household level. Sharing responsibilities between household level and TPS 3R management about percetage of processing organic waste should be implemented. It could level out household participation on solid waste management.